Phenylpyrazalopyrimidines as Tyrosine Kinase Inhibitors: Synthesis, Antiproliferative Activity, and Molecular Simulations - Bhupender S. Chhikara; Sajda Ashraf; Saghar Mozaffari; Nicole St. Jeans; Dindyal Mandal; Rakesh Kumar Tiwari; Zaheer Ul-Haq; Keykavous Parang (Molecules, 2020)
N1-(α,β-Alkene)-substituted phenylpyrazolopyrimidine derivatives with acetyl and functionalized phenyl groups at α- and β-positions, respectively, were synthesized by the reaction of 3-phenylpyrazolopyrimidine (PhPP) with bromoacetone, followed by a chalcone reaction with differently substituted aromatic aldehydes. The Src kinase enzyme assay revealed modest inhibitory activity (half maximal inhibitory concentration, IC50 = 21.7–192.1 µM) by a number of PhPP derivatives. Antiproliferative activity of the compounds was evaluated on human leukemia (CCRF-CEM), human ovarian adenocarcinoma (SK-OV-3), breast carcinoma (MDA-MB-231), and colon adenocarcinoma (HT-29) cells in vitro. 4-Chlorophenyl carbo-enyl substituted 3-phenylpyrazolopyrimidine (10) inhibited the cell proliferation of HT-29 and SK-OV-3 by 90% and 79%, respectively, at a concentration of 50 µM after 96 h incubation. The compound showed modest inhibitory activity against c-Src (IC50 = 60.4 µM), Btk (IC50 = 90.5 µM), and Lck (IC50 = 110 µM), while it showed no activity against Abl1, Akt1, Alk, Braf, Cdk2, and PKCa. In combination with target selection and kinase profiling assay, extensive theoretical studies were carried out to explore the selectivity behavior of compound 10. Specific interactions were also explored by examining the changing trends of interactions of tyrosine kinases with the phenylpyrazolopyrimidine derivative. The results showed good agreement with the experimental selectivity pattern among c-Src, Btk, and Lck.